The Effect of Teaching Integers through the Problem Posing Approach on Students' Academic Achievement and Mathematics Attitudes - ÖZDEMİR, AHMET ŞÜKRÜ (ANI YAYINCILIK, 2018)
Problem Statement: Throughout history, many changes have occurred in the field of mathematics education. These changes have also occurred concerning special topics that mathematics educators have constantly been searching. The significance of problem posing in mathematics teaching has increased recently with respect to its contributions to the teacher and the student. Thus, the problem posing approach is examined with respect to special topics. Study Purpose: The effect of teaching integers through the problem posing approach on sixth grade students' academic achievement and mathematics attitudes. Method: Mixed method, in which quantitative and qualitative research methods are used together, was conducted in the study. While the pre-test post-test control group model constituted the quantitative dimension of the study, the observation method and content analysis of students' work sheets were used for the qualitative dimension. The study groups consisted of a total of 69 participants, 34 of them were in the experimental and 35 of them were in the control group. Findings and Results: According to the findings of the study, there was a difference in favor of the experimental group with respect to the academic achievement levels; and there were no significant differences between two groups with respect to the attitudes towards mathematics. The observations indicated that the problem posing approach created a peaceful competition environment, and increased participation in the classroom. In addition, the student work sheets showed that participants' problem posing skills progressed, and they became aware of their mistakes. In conclusion, the problem posing approach had a positive effect on the academic achievement in teaching integers, but it did not have a significant effect on student attitudes towards mathematics. (c) 2018 Ani Publishing Ltd. All rights reserved
Keywords: mathematics education; problem posing; problem solving; teaching integers